Resident stem cells and regenerative therapy - Goldenberg, Regina Coeli dos Santos; Carvalho, Antonio Carlos Campos de (Academic Press, 2013)
In the last 3 decades, stem cells have greatly impacted the scientific and lay communities, providing huge advances in the treatment of devastating human diseases, including myocardial infarction, diabetes, muscular dystrophy, cystic fibrosis, cirrhosis, and osteoporosis. Alongside debates of induced pluripotent stem cells and embryonic stem cells has been the discovery of adult stem cells in many different tissues. While these organ resident or progenitor stem cells offer prospects to contribute to tissue regeneration, they also present challenges because of the complexity of organ structures. This book will present the main findings to date and the important factors to be considered when considering resident stem cells in regenerative therapies. Chapters on cardiac, brain, neural, liver, kidney, skeletal muscle, bone, pancreatic, skin, and lung resident stem cells will assist in defining the level of success that has been achieved and the direction for the road ahead. With contributions from leading laboratories, open questions related to resident stem cells and regenerative therapies will also be presented for debate. . Highlights basic research in tissue specific stem cells, experiments with animal models and clinical trials that are transforming the field of regeneration. . Provides a clear understanding of endogenous stem cells, their role in current regenerative therapies, and prospects for future research . Reports on the main-stream clinical approaches and in vivo experiments published in primary literature to help categorizes the advances in various aspects of regenerative therapy and illustrate opportunities for clinical applications.